Interferon-β induces hepatocyte growth factor in monocytes of multiple sclerosis patients. - Nicolas Molnarfi; Mahdia Benkhoucha; Kristbjörg Bjarnadóttir; Catherine Juillard; Patrice H Lalive (PLoS ONE, 2012)
Interferon-β is a first-line therapy used to prevent relapses in relapsing-remitting multiple sclerosis. The clinical benefit of interferon-β in relapsing-remitting multiple sclerosis is attributed to its immunomodulatory effects on inflammatory mediators and T cell reactivity. Here, we evaluated the production of hepatocyte growth factor, a neuroprotective and neuroinflammation-suppressive mediator, by peripheral blood mononuclear cells collected from interferon-β--treated relapsing-remitting multiple sclerosis patients, relapsing remitting multiple sclerosis patients not treated with interferon-β, and healthy volunteers. Using intracellular flow cytometry analysis, increased production of hepatocyte growth factor was observed in circulating CD14(+) monocytes from patients undergoing long-term treatment with interferon-β versus untreated patients. Complementary in vitro studies confirmed that treatment with interferon-β induced rapid and transient transcription of the hepatocyte growth factor gene in CD14(+) monocytes and that intracellular and secreted monocytic hepatocyte growth factor protein levels were markedly stimulated by interferon-β treatment. Additional exploration revealed that "pro-inflammatory" (CD14(+)CD16(+)) monocytes produced similar levels of hepatocyte growth factor in response to interferon-β as "classical" (CD14(+)CD16(-)) monocytes, and that CD14(+) monocytes but not CD4(+) T cells express the hepatocyte growth factor receptor c-Met. Our findings suggest that interferon-β may mediate some of its therapeutic effects in relapsing-remitting multiple sclerosis through the induction of hepatocyte growth factor by blood monocytes by coupling immune regulation and neuroprotection.